Application of quarter-sweep iteration for first order linear Fredholm integro-differential equations - Aruchunan, Elayaraja; Muthuvalu, M.; Sulaiman, J. (American Institute of Physics, 2013)
The main core of this paper is to analyze the application of the quarter-sweep iterative concept on finite difference and composite trapezoidal schemes with Gauss-Seidel iterative method to solve first order linear Fredholm integro-differential equations. The formulation and implementation of the Full-, Half- and Quarter-Sweep Gauss-Seidel methods namely FSGS, HSGS and QSGS respectively are also presented for performance comparison. Furthermore, computational complexity and percentage reduction analysis are also included and integrated with several numerical simulations. Based on numerical results, findings show the proposed QSGS method with the corresponding discretization schemes is superior compared to FSGS and HSGS iterative methods.